Advances in directional and linear statistics a festschrift for Sreenivasa Rao Jammalamadaka - Wells, Martin (Martin T.).; Sengupta, Ashis; SpringerLink (Online service). (Berlin Heidelberg Physica-Verlag, 2011)
The present volume consists of papers written by students, colleagues and collaborators of Sreenivasa Rao Jammalamadaka from various countries, and covers a variety of research topics which he enjoys and contributed immensely to.
Models for Axial Data -- Asymptotic Behavior of the Universally Consistent Conditional U-Statistics for Nonstationary and Absolutely Regular Processes -- Regression Models with STARMA Errors ? An Application to the Study of Temperature Variations in the Antarctic Peninsula -- The Generalized von Mises-Fisher Distribution -- A New Nonparametric Test of Symmetry -- A Semiparametric Bayesian Method of Clustering Genes Using Time-Series of Expression Profiles -- On Implementation of the Markov Chain Monte Carlo Stochastic Approximation Algorithm -- Stochastic Comparisons of Spacings from Heterogeneous Samples -- The Distributions of the Peak to Average and Peak to Sum Ratios under Exponentiality -- Least Square Estimation for Regression Parameters under Lost Association -- On Tests of Fit Based on Grouped Data -- Innovation Processes in Logically Constrained Time Series -- Laws of Large Numbers and Nearest Neighbor Distances -- Nonparametric and Probabilistic Classification using NN-balls with Environmental and Remote Sensing Applications -- Probabilistic Recurrence Relations -- On Some Inequalities of Chernoff-Borovkov-Utev Type for Circular Distributions -- Revisiting Local Asymptotic Normality (LAN) and Passing on to Local Asymptotic Mixed Normality (LAMN) and Local Asymptotic Quadratic (LAQ) Experiments -- Long Range Dependence in Third Order for Non-Gaussian Time Series -- Graphical Models for Clustered Binary and Continuous Responses.
Electronic reproduction.
Keywords: Mathematical statistics; Electronic books